Racismo de Estado e suas vias para fazer morrer - Oliveira, Lorena Silva (2018)
This work, by the concept of State racism, showed by Michel Foucault, seeks to present the ways in which the Brazilian State allows the black population to die, especially their youth. For this, it starts from the metaphor of the war to demonstrate that the warrior relationship, the war of races existing in the social body is reinserted within the state, and through the development of technologies of power, the state seeks to keep this war evident and deafening against black population, a silent war. We demonstrate the role played by knowledge in the process of constructing the conception of black individuals as a Non-Being and later a public enemy, so that the actions of the State against this population are understood as necessary to defend society and the lives worthy of protection and living. On this hand, racism is understood as a security device that condemns death and eliminates through sub-devices such as epistemic, imprisonment and physical annihilation of individuals by the police, this portion of the population. Moreover, we show that this whole process of murder has as its final expression the extermination of the black lives, which, converted into superfluous lives, expresses that biopolitics becomes increasingly a necropolitcs, a policy that subjugates life to the power of death.